A Review on Pulping, Bleaching and Papermaking Processes - Sharma, Nidhi; Bhawana; Godiyal, R. D.; Thapliyal, B. P. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*318.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904429);" role="presentation">This paper presents a concise overview of pulp and paper product<span dir="ltr" style="left: calc(var(--scale-factor)*335.83px); top: calc(var(--scale-factor)*318.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902088);" role="presentation">ion process, chemical constituents of the paper <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*331.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922173);" role="presentation">making biomass, <span dir="ltr" style="left: calc(var(--scale-factor)*144.86px); top: calc(var(--scale-factor)*331.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933896);" role="presentation">pulping and bleaching processes. Processes related to raw material preparation, washing of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939932);" role="presentation">pulp, <span dir="ltr" style="left: calc(var(--scale-factor)*95.30px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912153);" role="presentation">chemical recovery operations, s<span dir="ltr" style="left: calc(var(--scale-factor)*223.01px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920296);" role="presentation">tock preparation <span dir="ltr" style="left: calc(var(--scale-factor)*291.77px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*309.17px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902609);" role="presentation">papermaking <span dir="ltr" style="left: calc(var(--scale-factor)*364.15px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888086);" role="presentation">are described. <span dir="ltr" style="left: calc(var(--scale-factor)*423.19px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943263);" role="presentation">Significance of <span dir="ltr" style="left: calc(var(--scale-factor)*487.30px); top: calc(var(--scale-factor)*345.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915408);" role="presentation">chemical <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*358.25px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932823);" role="presentation">constituents of papermaking biomass such as lignin, cellulose, hemicellulose, extractives, ash, water solubility <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*371.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930125);" role="presentation">and alkali solubility towards papermaking is explained. <span dir="ltr" style="left: calc(var(--scale-factor)*297.53px); top: calc(var(--scale-factor)*371.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915751);" role="presentation">Reflections on different types of pulping processes such <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*384.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861605);" role="presentation">as soda, soda-<span dir="ltr" style="left: calc(var(--scale-factor)*128.78px); top: calc(var(--scale-factor)*384.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939389);" role="presentation">AQ and <span dir="ltr" style="left: calc(var(--scale-factor)*163.58px); top: calc(var(--scale-factor)*384.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923535);" role="presentation">Kraft pulping along with the necessary reactions have been provided. <span dir="ltr" style="left: calc(var(--scale-factor)*448.30px); top: calc(var(--scale-factor)*384.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892937);" role="presentation">Various sequences <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*397.85px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00562);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*85.46px); top: calc(var(--scale-factor)*397.85px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985788);" role="presentation">conventional, elemental chlorine free and total chlorine free bleaching <span dir="ltr" style="left: calc(var(--scale-factor)*392.83px); top: calc(var(--scale-factor)*397.85px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0192);" role="presentation">along with use of enzymes in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*411.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944526);" role="presentation">bleaching is portrayed. <span dir="ltr" style="left: calc(var(--scale-factor)*171.14px); top: calc(var(--scale-factor)*411.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.991725);" role="presentation">In addition, status of different types of <span dir="ltr" style="left: calc(var(--scale-factor)*339.67px); top: calc(var(--scale-factor)*411.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974577);" role="presentation">raw material used in Indian pulp and paper <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*424.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895737);" role="presentation">industry is also presented.